Copper-Catalyzed Regioselective Trifluoromethylthiolation of Pyrroles by Trifluoromethanesulfonyl Hypervalent Iodonium Ylide - Huang, Zhongyan; Yang, Yu-Dong; Tokunaga, Etsuko; Shibata, Norio (Organic letters, 2015)
The copper-catalyzed trifluoromethylthiolation of pyrroles with a trifluoromethanesulfonyl hypervalent iodonium ylide under mild conditions has been achieved. A broad set of pyrroles could be transformed to the corresponding products in moderate to excellent yields. The reaction mechanism is hypothesized.